Study on Anticollision Performance of Metal Bellows Connected Concrete Anticollision wall - LIN Menghan; MIAO Ruifeng; LI Lijun (Taiyuan Ligong Daxue xuebao)
[Purposes] Prefabricated concrete anticollision wall has been applied in expressway gradually because of its various advantages. [Methods] The metal bellows for connecting prefabricated concrete anticollision wall are designed, and their anticollision performances are studied by experiments and finite element (FEM) simulations. The failure form, stress process, and impact parameters of anticollision performance of prefabricated concrete under horizontal impact are analyzed. The effects of impact energy on crashworthiness are considered in terms of the root connection form, connection reinforcement spacing, and impact energy. [Findings] The results show that: Under the action of pendulum impact, a circular crack is produced at the back of the specimen and expands in all directions, the concrete is crushed at the impact location on the impact surface, and the root steel plate is detached from the base concrete; The damage mechanism, impact force time course curve, and span deflection time course curve of the FEM simulated specimen are consistent with those of the test results; With the increase of impact energy, the peak impact force of the member increases; The midspan deflection of the specimen can be reduced by increasing the connection between bottom angle steel and steel plate or increasing the quantity of connection reinforcement.